(untitled) (Journal of Pharmaceutical Negative Results, 2011)
Background: Pyrimidine and fused pyrimidine derivatives play an important role intherapeutic strategies. It is known to be most prominent structures found in nucleicacid, including uracil, thymine, cytosine, adenine, and guanine, which are fundamentalbuilding blocks for deoxyribonucleic acid (DNA) and ribonucleic acid (RNA).Materials and Methods: A series of 3-[2-amino-6-(substituted)-pyrimidin-4-yl]-6-(substituted)-2H-chromen-2-one derivatives were prepared by reacting salicylaldehydewith ethylacetoacetate in the presence of piperidine by Knoevenagel reaction as astarting material. The chemical structures were confirmed by means of FTIR (FourierTransform InfraRed Spectrophotometer-8400S), 1H NMR, and elemental analysis. Thedata of these synthesized compounds were submitted to National Institute of Health,USA, under the drug discovery program of NCI (National Cancer Institute) andscreened for anticancer activity at a single high dose (10−5 M) in full NCI 60 cell lines.Results: Unfortunately, the selected compounds have not shown any potent significantanticancer activity in the NCI 60 cell line screening. Conclusion: The compound (T2)found to be most efficient anticancer activity with selective influence on breast cancercell lines, especially on MCF7 cell line with a growth percentage of 33.63.